Preliminary study on FTIR analysis of microplastics in water samples of Erzeni River mouth, Adriatic Sea—Albania - Vanela Gjeci; Olta Cakaj; Flora Qarri; Kledi Xhaxhiu; Alketa Lame; Pranvera Lazo (Romanian Journal of Ecology & Environmental Chemistry)
There is a significant gap in the published literature regarding the characterization and analysis of microplastics (MPs) in the aquatic ecosystems of Albania. This study focuses on the delta of the Erzeni River as one of the major sources of anthropogenic pollution, including micro- and macroplastics, in the Albanian coastal area of the Adriatic Sea. After oxidative treatment of water samples with H₂O₂ and separation using the high-density method, identification of MPs was performed using spectroscopic and FTIR methods. Spectroscopic and FTIR analysis revealed the presence of MPs of the type PVC or PVC/MMT, nylon, PS, and PE in water samples. Spectral bands in the region of 400 cm-1 to 1100 cm-1 can be associated with the presence of synthetic rubber. The analysis presented in this study investigates the potential sources of MPs in coastal environments, based on the identification of plastic species. This research is the first of its kind in Albania's coastal area that serves as an important initial contribution to the development of a database dedicated to the assessment of MPs in this ecosystem. MPs in water samples from the delta of the Erzeni River that discharges into the Adriatic Sea. The objective of this study was to examine the morphological characteristics and classifications of MPs found in the research area, as well as to assess the consequences of their degradation.